2019
DOI: 10.1111/sms.13605
|View full text |Cite
|
Sign up to set email alerts
|

Does lean body mass equal health despite body mass index?

Abstract: Objective To determine the association between having simultaneously high body mass index (BMI) and high relative lean body mass (LBM) and cardio‐metabolic risk factors, metabolic syndrome (MetS), and diabetes in adults. Materials and Methods A cross‐sectional analysis was performed on 4982 adults aged 19‐85 years that participated in the National Health and Nutrition Examination Survey (cycles 1999‐2000‐2005‐2006). The primary exposure variable was categorization into four groups: (a) Low‐BMI/Low‐LBM, (b) Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is interesting that FFM connected with a 20 % increased probability of CVD mortality. Later Colpitts and co-authors (Colpitts et al, 2019) indicated that: 1) BMI is a strong predictor of metabolic syndrome and diabetes; 2) attention should be paid to muscle quality (increasing oxidative abilities) but not greater FFM for prevention further cardio-metabolic risk factors. After 60 days of the research there was an increase of FFMI in the main group by 0.3 kg/m2 and in the control group by 0.4 kg/m2, but these data were not statistically significant (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that FFM connected with a 20 % increased probability of CVD mortality. Later Colpitts and co-authors (Colpitts et al, 2019) indicated that: 1) BMI is a strong predictor of metabolic syndrome and diabetes; 2) attention should be paid to muscle quality (increasing oxidative abilities) but not greater FFM for prevention further cardio-metabolic risk factors. After 60 days of the research there was an increase of FFMI in the main group by 0.3 kg/m2 and in the control group by 0.4 kg/m2, but these data were not statistically significant (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…44 Thus, individuals with increased muscle mass (e.g., athletes), may have a high BMI without an associated increase in cardiometabolic disease risk. 45 Finally, certain measurements of metabolic data such as blood pressure, hemoglobin A1c, and cholesterol were only taken at later waves (i.e., Waves IV and V), limiting analysis of association between screen time and cardiometabolic disease risk over time. There is also the potential for unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Dada et al (15) found that higher BMI was associated with improved performance of occupational tasks requiring strength and power, arguably a reflection of greater LBM. However, to the contrary, research has also found that irrespective of LBM, maintaining a BMI of less than 30 kg·m −2 is ideal when considering risk factors for cardiometabolic disease (13). Research has also identified clear associations between BMI and physical activity.…”
Section: Discussionmentioning
confidence: 99%